Islam Our Choice: Portraits of Modern American Muslim Women by Debra L. Dirks & Stephanie Parlove, eds. (USA: amana publications, 2003. 298 pages.) (American Journal of Islam and Society, 2004)
This book is a delightful read. The somewhat unoriginal title (compilationsof conversion accounts under the title Islam Our Choice have been aroundfor several decades, including stories that date back to the mid-twentiethcentury) belies the original and unique stories told within. However, thesewords might be rather startling for many non-Muslims, and thus piquetheir curiosity enough to pick up the book and inquire further.Islam Our Choice, aimed primarily at non-Muslim Americans, tellsthe stories of fellow Americans who have chosen to follow a different pathbut who are still Americans. The authors express the hope that “each non-Muslim American reader will probably be able to relate to and identifywith the pre-Muslim background of at least one of the authors” (p. 2). Theinclusion of family photos and illustrations adds to the book’s visualappeal and shows the contributors as ordinary Americans who are at homewith their new identity as Muslims.Although the contributors cover a wide range of geographical locations,levels of education, and career paths, their ethnic and religious backgroundscover a narrower range. Most of the respondents were former Christians ofvarying denominations, and most are white; one African-American womanalso contributed her story. It is now well known that there are Jewish,Latinos/Latinas, and Native American converts, and, hopefully, their storieswill be told in the near future in order to present a fuller picture of how Islamis reaching all sections of American society.The book opens with a brief overview of Islamic faith and practice, Islamin America, and a comparison between the position of women in modernAmerica and in Islam. This sets the scene, as it were, for readers who may beunfamiliar with the Muslim world and with Muslim communities in the West.Written according to the introduction’s general outline, each chapterrelates the story of an American woman who has come to Islam. All contributorsoffer insight into their childhood worlds, whether they were cozyand relatively uneventful, or dogged by poverty and such family troublesas alcoholism. Debra L. Dirks introduces the Mennonite culture fromwhich her family comes, and Khadijah R. Beruni sheds light on the twoworlds of her childhood in an extended African-American family: living ...